Automatic location of IC design errors using an e-beam system - BOLAND, FRANCIS MORGAN (IEEE, 1988)
The ADVICE system discussed is an enhanced CAD (computer-aided design) linked E-beam tester to locate automatically design errors on custom VLSI devices. The goal is met by building a set of procedures to drive the interactive electron-beam debugging (EBD) system according to the strategies devised by the algorithms based on fault dictionary/hierarchical probing algorithm mixed search
International Test Conference: 1988
PUBLISHED
Keywords: E-beam tester; ADVICE system; VLSI devices